3-({4-[(2-Methylbenzylidene)amino]5-sulfanylidene-1H-1,2,4-triazol-3-yl}methyl)-1,3-benzoxazol-2(3H)-One - Aydin, Abdullah; Hekimoglu, Nuray; Akkurt, Mehmet; Onkol, Tijen; Cicekli, Solen Urlu; Buyukgungor, Orhan (Int Union Crystallography, 2013)
In the title compound, C18H15N5O2S, a weak intramolecular C-H center dot center dot center dot S hydrogen bond results in a small dihedral angle of 3.71 (9)degrees between the methylphenyl and triazole rings, which, in turn, form dihedral angles of 80.09 (8) and 77.32 (8)degrees, respectively, with the benzoxazolone mean plane. In the crystal, N-H center dot center dot center dot O hydrogen bonds link molecules into chains along [001], and weak C-H center dot center dot center dot N hydrogen bonds and pi - pi interactions between the five-and six-membered rings [centroid-centroid distances = 3.5074 (11) and 3.616 (1) angstrom] consolidate the crystal packing.
Aydin, Abdullah/0000-0003-2805-9314;